2003
DOI: 10.1103/physrevd.68.064012
|View full text |Cite
|
Sign up to set email alerts
|

Massive scalar states localized on a de Sitter brane

Abstract: We consider a brane scenario with a massive scalar field in the five-dimensional bulk. We study the scalar states that are localized on the brane, which is assumed to be de Sitter. These localized scalar modes are massive in general, their effective four-dimensional mass depending on the mass of the five-dimensional scalar field, on the Hubble parameter in the brane and on the coupling between the brane tension and the bulk scalar field. We then introduce a purely four-dimensional approach based on an effectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 20 publications
10
50
0
Order By: Relevance
“…The derived scale function and warp factor are employed in the five-dimensional Klein-Gordon equation describing the massive scalar field whose wave function will depend on the cosmic time and on the extra-dimension. Our results agree with those obtained by Langlois and Sasaki [23], who considered a test scalar field on a given background configuration and solved the Klein-Gordon equation in the bulk. They found an interesting relationship between the effective four-dimensional mass of the scalar states localized on the de Sitter brane and the five-dimensional mass.…”
Section: Introductionsupporting
confidence: 82%
“…The derived scale function and warp factor are employed in the five-dimensional Klein-Gordon equation describing the massive scalar field whose wave function will depend on the cosmic time and on the extra-dimension. Our results agree with those obtained by Langlois and Sasaki [23], who considered a test scalar field on a given background configuration and solved the Klein-Gordon equation in the bulk. They found an interesting relationship between the effective four-dimensional mass of the scalar states localized on the de Sitter brane and the five-dimensional mass.…”
Section: Introductionsupporting
confidence: 82%
“…From Eqs. (2.8), we readily see the local mass corresponding toS a is given by [16] 11) where the factor 3/2 in the original expression forS a is eliminated for later convenience. Alternatively, corresponding to S a , we have another local mass that excludes the contribution of the bulk cosmological constant, 12) In what follows, we focus on the matter part M , rather than on the whole massM .…”
Section: A Local Conservation Lawmentioning
confidence: 98%
“…In the bulk inflaton model with a quadratic potential [9][10][11][12], it has been shown that the bulk scalar field projected on the brane behaves exactly like a 4-dimensional field in the low energy limit, H 2 ℓ 2 ≪ 1, where H is the Hubble parameter of the brane, and the leading order correction gives the gradual energy loss from the scalar field to the bulk, giving rise to the dark radiation term [9,11]. Here, we discuss the relation between the dark radiation term appearing in this effective 4-dimensional description and the generalized dark radiation term given by the local mass in the bulk.…”
Section: Local Mass and The Effective 4-dimensional Descriptionmentioning
confidence: 99%
“…Since the coefficients in front the Legendre functions in (29) vanish when m = 0 and ω = −3i/2, it is possible to linearise the resonance condition about the zero mode solution (55). In particular, we can take…”
Section: Perturbed Zero Modementioning
confidence: 99%
“…These match the various bound state criteria obtained for a massive scalar field about a de Sitter brane in Refs. [27,28,29] (up to trivial differences in notation).…”
Section: Zero Couplingmentioning
confidence: 99%